Penerapan Pendekatan Metakognitif pada Mobile-Learning Sebagai Media Pembelajaran untuk Meningkatkan Pemahaman Siswa pada Materi Boga Dasar - Putri Rahayu; Desi Andreswari; Aan Erlansari; Boko Susilo (JSAI (Journal Scientific and Applied Informatics), 2024)
This research aims to develop a mobile-learning application as an Android-based learning medium that suits the needs and applicable curriculum by applying a metacognitive approach, as well as knowing the influence of mobile-learning users to increase students' understanding of basic culinary lessons. This research uses the R&D development method with the ADDIE model and the Prototyping system development method. This application provides interaction from students as users to carry out learning simulation exercises which are incorporated into the study room features so that they can support basic culinary learning and provide learning evaluation questions. Based on the comprehension achievement test carried out on 64 students at SMK Negeri 3 Bengkulu City, a significance result of 0.001 (<0.05) was obtained from the pre-test and post-test of the wilxicon signed-rank test, then Ha was accepted which shows that the metacognitive approach was applied in mobile-learning as a learning medium it influences aspects of students' understanding of basic culinary learning. The use of metacognitive approach features in mobile-learning applications helps students monitor their understanding. Keywords: Learning media, metacognitive approach, Mobile-learning, Android, Pre-test, Post-test, Basic Cooking